PENGARUH PENGUASAAN HUKUM OHM TERHADAP HASIL BELAJAR FISIKA SISWA PADA MATERI POKOK DAYA LISTRIK KELAS IX MTS PADANG LAWAS UTARA - Febriani Hastini Nasution (JURNAL PhysEdu (PHYSICS EDUCATION), 2023)
This research is purpose to see the effect of ohm law mastery to word the result of physics on the material of electric power at class nine of MTS. Swasta Baitur Rahman Parau Sorat. The population was all students in IX grade students of MTS Swasta Baitur Rahman Totaling 62 people. The technique in take sample in this research use total sampling. So, the sample in this research are all of the students in IX class MTS. Baitur Rahman. The research method used in this study is descriptive method and correlational. To analyzing the data, the authors define using test. The first analysis is to see the description generaliy and clearly about mean, median, modus, distribution frequency and histogram about two variables. The second stage is inferential analysis, which, is to test the hypotheses using “r” product moment and then used t-tes formula the result mean is 79,76 on X variable with the category of good and Y variable obtained for 80,85 with the category of best/very good. Through the calculation is done, t counting is 9,9547 and t tabel is bigger than t tabel (9,9547>1,671). It mean that there is a significant the effect ohm law mastery toward the result of physics on the material of electric power at the class nine students of MTS. Swasta Baitur Rahman.